Plume-subduction interaction forms large auriferous provinces. Issue 1 (December 2017) - Tassara, Santiago; González-Jiménez, José; Reich, Martin; Schilling, Manuel; Morata, Diego; Begg, Graham; Saunders, Edward; Griffin, William; O'Reilly, Suzanne; Grégoire, Michel; Barra, Fernando; Corgne, Alexandre
Abstract Gold enrichment at the crustal or mantle source has been proposed as a key ingredient in the production of giant gold deposits and districts. However, the lithospheric-scale processes controlling gold endowment in a given metallogenic province remain unclear. Here we provide the first direct evidence of native gold in the mantle beneath the Deseado Massif in Patagonia that links an enriched mantle source to the occurrence of a large auriferous province in the overlying crust. A precursor stage of mantle refertilisation by plume-derived melts generated a gold-rich mantle source during the Early Jurassic. The interplay of this enriched mantle domain and subduction-related fluids released during the Middle-Late Jurassic resulted in optimal conditions to produce the ore-forming magmas that generated the gold deposits. Our study highlights that refertilisation of the subcontinental lithospheric mantle is a key factor in forming large metallogenic provinces in the Earth's crust, thus providing an alternative view to current crust-related enrichment models. The lithospheric controls on giant gold deposits remain unclear. Here, the authors show evidence for native gold in the mantle from the Deseado Massif in Patagonia demonstrating that refertilisation of the lithospheric mantle is key in forming metallogenic provinces.